Organic geochemical and petrographical characteristics of the lower part of Sarmord Formation, M-2 Well, Miran Oil Field, Kurdistan, NE Iraq: Implications for hydrocarbon generation potential and thermal maturation - Fatah, Sardar S.; Salih, Danyar A.; Kalaitzidis, Stavros; Mohialdeen, Ibrahim M. J.; Khanaqa, Polla A. (Sulaimani Journal for Pure and Applied Sciences, 2020)
The Lower Cretaceous Sarmord Formation (Hauterivian–Barremian) has been investigated in this study. The selected M-2 Well is one of the wells belonging to Miran block, Sulaimani Governorate, Kurdistan Region of Iraq. The area of interest is situated in the High Folded Zone, Western Zagros Fold-Thrust Belt, being approximately 30 km far from Sulaimani City towards the northwest direction. The selected samples were analyzed by Rock-Eval pyrolysis, infrared spectroscopy, and also studied microscopically to determine the quality and quantity of organic matter, the level of thermal maturity, as well as the hydrocarbon generation potentiality. Rock-Eval pyrolysis data show that the total organic carbon for Sarmord Formation is between 0.83 wt.% to 1.55 wt.%, with an average value of 1.27 wt.%. The average and range of S1, S2, and genetic potential (S1+S2) are: 0.76 (0.55–1.09) mg HC/g rock, 0.82 (0.65 – 1.28) mg HC/g rock, and 1.58 (1.21 -2.37) mg HC/g rock, respectively. The average value of pyrolysable carbon (PC) and residual carbon (RC) are of 0.23 wt.% and 1.04 wt.%, respectively. The hydrogen index (HI) is between 47 and 98, with an average value of 66. The obtained data indicate that the Sarmord Formation has a satisfiable range of total organic carbon content, but the organic matter by itself has poor potential to generate hydrocarbons because of low amount of S2, HI, and PC. The Rock-Eval maturity parameters (Tmax and PI ) are undependable in this study. Because they are out of the acceptable range. The cutting samples in this well have been contaminated by solid drilling additives, which were identified during the petrographiocal study by their structure and low reflectance values. The double peaks of S2, solid drilling additives, are affected of disturbing maturity parameters of Rock-Eval data. The petrographic study proved that the samples mostly contain bituminite, which is disseminated predominantly within the clayey particles, with minor amounts of alginite. Additionally, weathered and degraded humic particles are interpreted as content of drilling mud. The kerogen types are mostly of Type II kerogen, because the vitrinite macerals are absent and we have an indication of alginite; which is one of precursos of formation of bituminite. This result is controversial with the graphical presentation of kerogen type by Rock-Eval and infrared microscopy, as they are interpreted as Type III gas-prone kerogen. The equivalent vitrinite reflectance for the studied section ranges between 0.73-0.81%, with the values close to 0.80% being more accurate as were measured in homogenous solid bitumens. The obtained values indicate maturation within the oil window. While based on infra red spectroscopy, maturation is between 0.80 to 1.10, suggesting to higher maturation level compared to vitrinite reflectance values.
Keywords: Sarmord Formation; Kurdistan; Miran Field; Hydrocarbon potentiality; Kerogen type